SOME OBSERVATIONS ON TASK SCHEDULING ALGORITHMS FOR DISTRIBUTED COMPUTING ON MULTIPROCESSORS - MAURYA, ASHISH KUMAR (IIT BHU VARANASI, 2018)
Abstract is available in content.
Keywords: SOME OBSERVATIONS ON TASK SCHEDULING; ALGORITHMS FOR DISTRIBUTED COMPUTING ON; MULTIPROCESSORS